Efeito do laser de baixa potência associado ao uso de carvão ativado no processo de reparo ósseo em tíbia de ratos - Sampaio, Alexandre Botelho de Abreu (2014)
The bone defects are caused by several factors and the repair process can be slow, where inflammatory and proliferative phases of remodeling of this tissue are extremely important for the quality of the repair. There are several therapies where the main is the surgery and in this case, the use of bone substitutes can be indicated. However the repair process may require assistance. Thus, the use of activated charcoal as bone substitute when the implementation of low-power laser to aid bone repair can be an alternative to these problems. The aim of this study was to verify the use of activated carbon as bone substitute and the interaction with the laser in the process of bone repair in rat tibias, assessing biochemical, histological and biomechanical changes. Material and methods: male wistar rats, 35 were used between 150 g to 200 g, with 3 months of age. The animals were anesthetized with ketamine hydrochloride and Association (90mg/Kg and 10mg/Kg, IP). Once anesthetized, the animals were put on surgical table, the skin was dissected and were made monocortical bone defects in the central region of the right tibia of mice. Immediately after surgery the rats were randomized and divided into the following groups: control (CTL), untreated Injury (NT), Lesion treated with activated carbon (CA), Lesion treated with association of activated carbon and laser 830nm, 6J-100mW (CA+L) and injury treated with Hydroxyapatite (HA). After 28 days the animals were euthanized with overdose of the same anesthetic, blood was collected and the tibia was taken for biochemical, histological and biomechanical analysis. Results: the NT group reduction in bending forces and histological changes related to disorganization of the tissue. The groups showed no CA+L and HA improves mechanical properties, however, the CA+L group presented histological aspects of improvement. Only the CA group presented better flexion forces, related with improvement of histological aspects and reduced levels of alkaline phosphatase. The NT groups, CA+L and HA presented high alkaline phosphatase levels. Conclusion: the use of activated carbon seems to improve the bone repair induced in this study. The laser association with activated carbon showed no improvement of biomechanical properties in spite of the histological results have a better aspect.